Stock vs. stock-warrant units: evidence from seasoned offerings - Byoun, Soku; Moore, William T. (Journal of Corporate Finance, 2003)
Recent theories based on sequential financing and information signaling reveal a special role for warrants. Data from initial public offerings (IPOs) of stock-warrant units have been used to test the theories, and we extend the analysis to seasoned offerings. Consistent with predictions from both families of theories, we find that issues made by smaller and younger firms are more likely to involve stock-warrant units, and firms with greater stock price volatility are more likely to issue units in seasoned offerings. Moreover, firms with relatively high levels of long-term debt, and those whose issues are underwritten by less prestigious underwriters are more likely to employ stock-warrant unit financing. Consistent with information signaling, we find that firms with high managerial ownership are more likely to issue units. Firms that include warrants in their stock offerings are predicted to have experienced higher abnormal stock returns than if they had issued shares alone. Thus, consistent with both theoretical explanations, some firms can reduce capital costs by adding warrants to shares in seasoned offerings.